2015
DOI: 10.5858/arpa.2014-0624-oa
|View full text |Cite
|
Sign up to set email alerts
|

Cancer as the Disintegration of Robustness: Population-Level Variance in Gene Expression Identifies Key Differences Between Tobacco- and HPV-Associated Oropharyngeal Carcinogenesis

Abstract: Context Oropharyngeal squamous cell carcinoma (OPSCC) is associated both with tobacco use and human papillomavirus (HPV) infection. It is argued that carcinogen-driven tumorigenesis is a distinct disease from its virally-driven counterpart. We hypothesized that tumorigenesis is the result of a loss of genotypic robustness resulting in an increase in phenotypic variation in tumors compared to adjacent histologically normal tissues, and that carcinogen-driven tumorigenesis results in greater variation than their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Recently, more and more studies have indicated that microRNAs are associated with tumorigenesis and development and that microRNAs play important roles in a variety of biological processes; their dysregulation may be crucial to cancer initiation, progression and treatment outcome . Some microRNAs were also reported to be associated with BC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more and more studies have indicated that microRNAs are associated with tumorigenesis and development and that microRNAs play important roles in a variety of biological processes; their dysregulation may be crucial to cancer initiation, progression and treatment outcome . Some microRNAs were also reported to be associated with BC.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that genes with high variability of expression are often associated with disease phenotypes [ 33 , 34 ]. Notably, the variance of gene expression in cancer tissues is higher than that in normal tissues [ 35 37 ]. We applied this insight that gene expressions in cancer tissues are heterogenous while their expressions in normal tissues are conserved, for distinguishing uterine leiomyosarcoma from normal uterine tissue and leiomyoma.…”
Section: Discussionmentioning
confidence: 99%
“…Each perturbation can be represented as an expression profile , where each gene is assigned a number corresponding to the degree of up‐ or down‐regulation relative to control (e.g., the difference of mean expression values); or this can be further processed by discretizing the values into a signature , defined here to mean the sets of significantly up‐ and down‐regulated genes. Though less commonly used, one could alternatively consider differential variance, or drug‐induced changes in the gene–gene covariance, also called differential coexpression (see Figure (c)). Several publicly available resources are worth mentioning here.…”
Section: Quantifying and Representing Drug Spacementioning
confidence: 99%